Effect of Bigger Ginger Extract on Reduction of Blood Sugar Rate of Glucose Induced Mice - Nurdin Nurdin; Asmawati Asmawati; Sitti Hadijah; Ratnasari Dewi; Widarti Widarti; Muhammad Nasir (Jurnal Media Analis Kesehatan, 2023)
To date, the government and people of Indonesia are still facing health problems. Diabetes, also known as diabetes mellitus, is one of the most common diseases among Indonesians. Some rhizome spices that have antidiabetic potential, one of which is elephant ginger. The purpose of this study was to determine the effectiveness of bigger ginger extract on reducing blood glucose levels in mice. This type of research is an experimental study to determine the effectiveness and concentration of bigger ginger extract on blood glucose levels in mice induced with glucose. Based on the results obtained, Bigger Ginger Rhizome Extract (Zingiber officinale var. Rosc.) has the potential to reduce blood sugar levels in mice with an average reduction value where 5% b/v extract decreased by 48.69%, 10% b/v extract decreased by 50% and 15% b/v extract decreased by 55%. The concentration of 5% b/v in Bigger Ginger Rhizome Extract (Zingiber officinale var. roscoe) shows an optimal reducing effect